Two new species of Chaetonotus (Gastrotricha, Chaetonotida, Chaetonotidae) from Japan TAKAHITO G. SUZUKI & HIDETAKA FURUYA (Japan) - Suzuki, Takahito G.; Furuya, Hidetaka (Zootaxa, 2011)
Two new species of freshwater gastrotrichs are described from a pond in Osaka, Japan. Chaetonotus retiformis n. sp. is a medium size species attaining a length of 180 μm, characterized by a three-lobed head with a single tuft of sensory cilia on each side and small scales with four long spines on the base of each member of the furca. Chaetonotus machikanensis n. sp. is a small size species attaining a length of 110 μm in length, characterized by a five-lobed head with a two tufts of sensory cilia on each side and large scales with long barbed spines.